Social research matters : a life in family sociology - Brannen, Julia (Sociology of children and families series., 2019)
Drawing from forty years of experience, Julia Brannen offers an invaluable account of how research in family studies is conducted and 'matters' at particular times. An exceptional resource for family scholars and those interested in the methodology of social research.